Home-based laboratory experiences during COVID-19 pandemic in undergraduate biochemistry students - Velarde, Victoria; Casado-Barragán, Felipe; Thamar, Michelle; Rands, Vicky F.; Gonzalez, Alexis A. (Frontiers in Education, 2022)
The coronavirus pandemic (COVID-19) pointed out new challenges to teaching in laboratory-based disciplines such as chemistry, biology and biochemistry with on-site practical sessions interrupted or suspended during 2020 and 2021. Observation and experimentation are part of education in science-based disciplines and provide necessary skills for professional and academic careers. In an effort to solve this disruption to experimental observations, we designed a set of home-based experiences related to chemistry and biochemistry. These included visual identification of lipids, sugars, proteins and DNA in biological samples using materials easily found at home such as alcohol, soap and oil, among others. Each activity was documented with smartphones and discussed in a final portfolio. Fifty-two students were part of an introductory cell biochemistry course. The home-based laboratories were organized into 2.5-h sessions that. included lab session, a post lab session, and a period for preparing the experiment at home. Thirty-six (17 men and 19 women) students answered a survey designed to assess three major domains: 1) student´s demographics and home environment 2) general perceptions of the laboratory activities, and 3) specific perceptions of each laboratory activity. Sixty two percent of the students thought that these activities helped them to understand how to isolate and identify macromolecules. Eleven percent said these home activities did not contribute to their understanding while 27% stated the activities were not significant for the topic. In-house experiments may provide a complementary tool for the understanding of main concepts in biochemistry along with improving skills in scientific thinking.